When the State Remains Silent: Media Framing and the Politics of Femicide in Indonesia - Vellayati Hajad; Ikhsan Ikhsan; Herizal Herizal (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2026)
This study explores the intersection between media discourse and policy inaction concerning femicide in Indonesia. Despite increasing cases of lethal violence against women, the term "femicide" remains absent mainly in state narratives and legal frameworks. The objective of this research is to examine how Indonesian online news media frame femicide cases and to analyze why these narratives fail to influence policy responses. Methodologically, the study employs a qualitative approach using Critical Discourse Analysis (CDA) and Multiple Streams Framework (MSF). A purposive sample of 20 news articles from major Indonesian news outletsÂ  and reports from women's rights organization was analyzed. CDA was used to identify dominant discursive patterns, actor representation, and silencing strategies, while MSF was applied to understand why femicide has not been translated into public policy. The findings reveal that media coverage tends to individualize cases, focusing on sensational elements and moral panic rather than systemic gender-based violence. Government officials are rarely cited, and policy solutions are virtually absent from the discourse. The analysis also shows that although the problem stream (public awareness) is present, the policy stream (available solutions) and political stream (elite will) remain disconnected, hindering agenda-setting. The study concludes that a formal policy response does not reflect institutional inertia and a more profound gendered political silence. It recommends integrating gender-sensitive terminology in official discourse, enhancing collaboration with civil society, and institutionalizing femicide as a category in national crime data and law.